مقاصد سُورة الإنسان وخَوَاصها: دراسةٌ حديثيةٌ تحليليةٌ - Adnan Mohd Abdullah Shalash (the Department of Islamic Thought and Culture NUML, 2024)
Surah Al-Insan came to show the impact of the many heavenly laws in declaring the status of man, and it mentioned the creation of Adam and what God - the Almighty - bestowed upon His servants and His rulings in their creation. She was interested in talking about the conditions of the afterlife, especially the bliss of the righteous in the abode of eternity and bliss. The surah opens by talking about the principle of creating man, providing him with the senses of hearing and sight, and guiding him to the path, then dividing him into two categories: the thankful and the ungrateful, and talking about the reward of the thankful and the ungrateful, and describing Paradise and Hell. Then she praised the deeds of the thankful, such as fulfilling a vow, providing food for the sake of God, and fearing the punishment of God Almighty, and she added that by describing what they have with their Lord of heaven, reward, favor, and honor. Then she explained the source of the revelation of the Qur’an, and the Prophet - may God bless him and grant him peace - commanded beautiful patience, remembrance of God Almighty, and praying the night prayer. She mentioned something contained in the previous surah; It is Surah Al-Qiyamah, which is: loving this immediate world and abandoning the afterlife and threatening them with replacing others like them if they persist in disbelief and stubbornness. Then the Noble Surah concluded by declaring that the Noble Qur’an is a reminder and admonition to all human beings, urging them to believe and act according to what it says. In this article, the discussion will revolve around the purposes of the Surah, the reason for its revelation, its virtues, its characteristics, and the lessons learned from it, and the hadiths related to it will be studied according to the hadith tradition.